Damages of orthotropic bridge deck surfacing : forensic investigation, remedial work and performance monitoring - Widyatmoko, Iswandaru (Penerbit Universiti Kebangsaan Malaysia, 2021)
Conventional mastic asphalt typically lasts for more than two decades when being used as bridge surfacing. However substantial increase in heavy goods traffic and higher axle loading has led to some severe cracks in the surfacing during the first ten years since opening to traffic. A forensic investigation into the defects was subsequently carried out. The investigation comprised site inspection, reviewing available records, laboratory testing, designing new surfacing system and recommending remedial actions. The site inspection identified structural and functional damages, which were subsequently assessed in the laboratory on samples taken from site followed by detailed analysis. Laboratory assessments included stiffness, tensile strength and rheology of the existing mastic asphalt surfacing and the waterproofing layer. These suites of testing were followed by Finite Element Models (FEMs) which were developed specifically to analyze movements of the deck, including the cantilever and the main decks, for a range of traffic levels and speeds, considering the mechanical properties determined from the laboratory tests. From the review of literatures and worldwide case studies, three alternative surfacing system options were identified. Prediction of the residual life of the existing surfacing and the projected life of the recommended replacement systems were analyzed. The effect of super single wheel loading on the proposed system was also assessed. Based on the relative performance of these options, recommendations were presented to improve the surfacing design for use in the interim maintenance and remedial works. Follow up works included monitoring the in service performance of the interim solution since opening to traffic. For the future major rehabilitation works, three alternative options have been advised to replace the current surfacing system. The benefits of each of these options have also been presented to assist with decision making, in consideration of the cost and the technical side.